A Circ-0007022/miR-338-3p/Neuropilin-1 Axis Reduces the Radiosensitivity of Esophageal Squamous Cell Carcinoma by Activating Epithelial-To-Mesenchymal Transition and PI3K/AKT Pathway - Zhang, Junpeng; Yu, Yanyan; Yin, Xiaoyang; Feng, Lei; Li, Zhe; Liu, Xiaomeng; Yu, Xinshuang; Li, Baosheng (Frontiers in Genetics, 2022)
Radiotherapy resistance is an important cause of treatment failure in esophageal squamous cell carcinoma (ESCC). Circular RNAs have attracted a lot of attention in cancer research, but their role in ESCC radiosensitivity has not been elucidated yet. Here, we aimed to evaluated the functional impacts of circ-0007022 on ESCC radiosensitivity. In this study, a stable radiotherapy-resistant cell line was established and verified by a series of functional experiments. Subsequently, high-throughput sequencing revealed that circ-0007022 was significantly overexpressed in the radiotherapy-resistant cell line and this conclusion was verified in ESCC patients' tumor tissues by real-time quantitative PCR. Moreover, loss-of-function and overexpression experiments in vitro and in vivo revealed that, after irradiation, the abilities of proliferation and migration in circ-0007022-overexpressing stable transgenic strain were significantly higher than that in circ-0007022-knockdown stable transgenic strain. Additionally, RNA Immunoprecipitation, RNA pull-down, luciferase reporter assays, and fluorescence in situ hybridization experiments demonstrated the mechanism of how circ-0007022 could sponge miR-338-3p and upregulate downstream target of miR-338-3p，neuropilin-1 (NRP1). Moreover, NRP1 led to poor prognosis for ESCC patients receiving radiotherapy, and NRP1 knock-down enhanced radiosensitivity of ESCC cells. Furthermore, circ-0007022 overexpression activated Epithelial-to-mesenchymal transition and PI3K/Akt pathway, and NRP1 knock-down could reversed this phenomenon. Finally, Akt Inhibitor reversed circ-0007022’s role in radiotherapy in ESCC cells. Taken together, the circ-0007022/miR-338-3p/NRP1 axis enhances the radiation resistance of ESCC cells via regulating EMT and PI3K/Akt pathway. The new circRNA circ-0007022 is thus expected to be a therapeutic target for ESCC patients.